A study of energy efficiency building lighting system design - Ahmad, Mohd Hafiez (2013)
A considerable portion of the energy consumed in the electrical system in the world today is converted to artificial lighting. Light is essential to harmony between the activities of people in the contemporary world. With the increase in the energy consumption by different segments in relation to the difficulty of generation, it is possible to see the importance of efficient ways of lighting. This research discusses the performance of different lighting system in the Masjid Tanah Community College (MCTT) and saving the energy consumption in the laboratory lighting application. DIAlux software is used to study and evaluate the efficiency lighting scheme through the three (3) different type lighting system. DIALux 4.10 Lighting Wizard software is used to design and evaluate artificial lighting scheme with similar illumination abilities for the same office space through the use of different types of lamps and the simulation results are highlighted. Its cost effectiveness is also studied. The impact of use of natural lighting and artificial lighting on heating, ventilating and air conditioning (HVAC) system is examined and highlighted. The major findings in this research are the energy-efficient lighting design could still be achieved without sacrificing the visual comfort and quality of lighting and replacement of older fixtures with new luminaries can improve.